2017
DOI: 10.2174/1389557516666160418122701
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Retraction Agents – in vivo and in vitro Studies into their Physico-Chemical Properties, Biocompatibility with Gingival Margin Tissues and Compatibility with Elastomer Impression Materials

Abstract: Gingival margin retraction/displacement (GMR/D) is a commonly accepted procedure in restorative dentistry. Of the various retraction methods, the chemo-mechanical approach with retraction media and chemical retraction agents (ChRAs) is mostly used. Different local and/or systemic side effects were observed after "chemical attacks" from these retraction agents. Moreover, no consensus exists as to the compatibility of chemical agents with different impression materials. This paper reports the findings of in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…8 Several studies have investigated the effect of gingival displacement medicaments on the physical properties of impression materials. 1,5,6,[9][10][11][12][13][14][15] Negative effects of ferric subsulfate, ferric sulfate, and aluminum chloride on the polymerization and tear strength of different types of final impression materials have been demonstrated. 9,12 This is possibly due to sulfur that delays or inhibits polymerization.…”
mentioning
confidence: 99%
“…8 Several studies have investigated the effect of gingival displacement medicaments on the physical properties of impression materials. 1,5,6,[9][10][11][12][13][14][15] Negative effects of ferric subsulfate, ferric sulfate, and aluminum chloride on the polymerization and tear strength of different types of final impression materials have been demonstrated. 9,12 This is possibly due to sulfur that delays or inhibits polymerization.…”
mentioning
confidence: 99%
“…However, their mechanism of action has not been completely clarified yet. The results presented in the previous studies based on in vitro experiments have expanded the knowledge on the action of vasoconstrictive retraction agents in primary HGFs (1,26,29). Through the assessment of selected oxidative stress markers, such as lipid peroxidation (the concentration of malondialdehyde (MDA)), protein damage (-SH), colony formation, and the expression of manganese superoxide dismutase (MnSOD), it was concluded that the experimental gels induced oxidative changes in primary HGFs at the lowest level.…”
Section: Introductionmentioning
confidence: 80%
“…Table I shows their characteristics. These chemicals were diluted with Dulbecco's modified Eagle's medium (DMEM) to 1:20 ratio, which was further studied based on our previous studies (1,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy gingival epithelial cells and epithelial attachment constitute a natural physical barrier protecting the connective tissues and minimizing the level of damage. Additionally, the aggressive clinical action of chemical hemostatic agents may be less intense because their concentration is diluted by either natural gingival fluids, saliva, or water spray . However, the findings of the present in vitro study suggest that the risk of tissue damage is high with the use of hemostatic agents such as Astringedent, Hemox‐A, Hemodent, Vicostat, and 3M ESPE Astringent Retraction Paste.…”
Section: Discussionmentioning
confidence: 99%